Superwomen: Battles of Work-Family - Chrisanty Victoria Layman; Jacob Donald Tan (APMBA (Asia Pacific Management and Business Application), 2022)
The purpose of this paper to examine the influence of work characteristics and family characteristics towards interference in work and interference in family amongst working Indonesian women.The data for this study were collected using questionnaire directed towards working women who are still holding family related roles. A total of 209 respondents was used in this study. Data analysis was done using Structural Equation Modelling approach using the help of SPPS AMOS. The study found that work characteristics and family characteristics all influence work interference family and family interference with work. In addition, the support of family, partner, network, and other services plays at a significant moderate to either affect positively or negatively towards work interference to family or family interference to work. The study's findings showcased women are involved in the gig economy, when like in the case due the pandemic, many women jump into work for additional income for their households.  With working women awareness towards work interference with family, workplaces for women should need to put in place policies that would not let the work compete to her priorities in family. The study showcased that there is a significant moderating effect of support towards work interference with family and family interference with work. And both variable work interference with family and family interference with work could be studied separately.